Exploring the interprofessional relationships between community pharmacists and general practitioners undertaking a collaborative medicines management service - Sadler, Stacey Claire (2006)
To improve the outcomes of drug therapy, there is increasing interest in the community pharmacist providing medicines management services (MMS) (Department of Health, 2000b, 2003a). In 2001, the Department of Health funded the Community Pharmacy Medicines Management Project (CPMMP) to evaluate the introduction of a community pharmacy led MMS.